A Kikuchi-Fujimoto Disease Case Mimicking T Cell Lymphoma with Prolonged Fever. (9th December 2014) - Yadigar, Serap; Balkan, Ilker Inanc; Saltoglu, Nese
Abstract : Kikuchi-Fujimoto disease (KFD) is a self-limited disease characterized by necrotizing lymphadenitis. Although cervical lymphadenitis in young women is the most familiar clinical presentation, it may take place in the etiology of fever in cases presenting with fever of unknown origin. A 33-year-old male case admitted with fever, nausea, vomiting, weight loss, and leukopenia for one month, subsequently developing axillary lymphadenopathy during followup, diagnosed as KFD with typical histopathological findings, and showing full recovery after the excision of lymph node was presented in this report.